An interactive teaching module for increasing undergraduate physiotherapy students' cultural competence: A quantitative survey. (19th September 2020) - Fryer, Caroline; Edney, Sarah; van Kessel, Gisela
Abstract: Objectives: To provide safe and effective healthcare, physiotherapists must be aware of, and able to appropriately respond to, the individual needs of their clients. Cultural competence is an essential part of the curriculum to prepare physiotherapy students for their graduate practice. The primary aim of this study was to investigate the effectiveness of a 4‐week educational intervention to increase the perceived cultural competence of undergraduate physiotherapy students and whether effectiveness changed as students progressed in their education. Secondary aims were to understand if a clinical placement prior to the course intervention, or the student's cultural background, influenced the effectiveness of the intervention. Methods: A prospective cohort study was conducted with 73 students in their second year of an Australian Bachelor of Physiotherapy programme who participated in a 4‐week tutorial module to develop their cultural competence. Perception of cultural competence was measured at three time points (pre, post, post 18 months) using the Cultural Intelligence Scale questionnaire which assesses metacognitive, cognitive, motivational and behavioural domains. Participant and their parents' country of birth data were collected. Results: Cultural intelligence scores for the cohort significantly increased from pre‐ to post‐intervention (mean change 0.4, p < 0.001). A 3‐week clinical placement prior to the teaching intervention had no effect on the change in scores. Students who were not born in Australia, or who had a parent not born in Australia, demonstrated less change in overall cultural intelligence score than Australian‐born participants. Conclusion: Undergraduate physiotherapy students at an Australian university can increase their perceived level of cultural competence by participating in a 4‐week classroom‐based tutorial module, and this effect can be sustained over an 18‐month period. Exposure to cultural diversity is not sufficient by itself for a change in perceived cultural competence. However, classroom‐based teaching needs to be responsive to the cultural characteristics of the students.